Problems Of Financing SMES In Ghana: A Case Study Of Kwahu West And Birim Central Municipalities - OPPONG, Frank Adams; AGYEMANG, Oscar Opoku AGYEMANG; KYEI, Kwabena (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:Considered peripheral to economic and public policy in the past, the role of small and medium enterprises (SMEs) has recently been highly recognized as a critical factor in the economic growth and development strategies of countries worldwide. This notwithstanding, SMEs continue to face a myriad of challenges about financing. The study, among others, sought to explore financing challenges facing SMEs in Kwahu West and Birim Central Municipalities of Ghana.Methodology:A survey questionnaire was used to collect data from 200 senior officers of SMEs in the selected municipalities. Descriptive statistics, Pearson's correlation, and linear regression statistical techniques were employed in data analysis.Findings:The findings indicated that most SMEs in both municipalities were sole proprietorships and needed more capacity and expertise to fulfill the requirements for external funding. Also, SMEs need more access to credit, adequate managerial expertise, information asymmetry, and transaction costs. In addition, the findings indicated that SIZE of SME and SME age have a positive and significant relationship with SME financing. Moreover, alternative funding sources, including equity sources provided by the alternative market of the Ghana Stock Exchange, were identified.Implication:The study concluded that although the financing challenges are real and numerous, stakeholder engagements and general governmental support can help push the growth and sustainability of SMEs. It was recommended that the National Board for Small-Scale Industries compile a register of all SMEs in the country and provide a platform for publishing their annual financial reports.